FUNDC1 regulates mitochondrial dynamics at the ER–mitochondrial contact site under hypoxic conditions. (4th May 2016) - Wu, Wenxian; Lin, Chunxia; Wu, Keng; Jiang, Lei; Wang, Xiaojing; Li, Wen; Zhuang, Haixia; Zhang, Xingliang; Chen, Hao; Li, Shupeng; Yang, Yue; Lu, Yue; et al.
Abstract: In hypoxic cells, dysfunctional mitochondria are selectively removed by a specialized autophagic process called mitophagy. The ER–mitochondrial contact site (MAM) is essential for fission of mitochondria prior to engulfment, and the outer mitochondrial membrane protein FUNDC1 interacts with LC3 to recruit autophagosomes, but the mechanisms integrating these processes are poorly understood. Here, we describe a new pathway mediating mitochondrial fission and subsequent mitophagy under hypoxic conditions. FUNDC1 accumulates at the MAM by associating with the ER membrane protein calnexin. As mitophagy proceeds, FUNDC1/calnexin association attenuates and the exposed cytosolic loop of FUNDC1 interacts with DRP1 instead. DRP1 is thereby recruited to the MAM, and mitochondrial fission then occurs. Knockdown of FUNDC1, DRP1, or calnexin prevents fission and mitophagy under hypoxic conditions. Thus, FUNDC1 integrates mitochondrial fission and mitophagy at the interface of the MAM by working in concert with DRP1 and calnexin under hypoxic conditions in mammalian cells. Synopsis: In response to hypoxia, mitophagy receptor FUNDC1 associates with ER‐resident protein calnexin and thereby accumulates at the ER–mitochondrial contact site; this allows for DRP‐1 recruitment and thus mitochondrial fission. FUNDC1 accumulates at the ER–mitochondrial contact site (MAM) by association with calnexin in response to hypoxia. FUNDC1 mediates mitochondrial fission in response to hypoxia. FUNDC1 binds to DRP1 for mitochondrial fission during hypoxia. FUNDC1 is the molecular link that integrates mitochondrial fission and mitophagy at the interface of the MAM. Abstract : In response to hypoxia, mitophagy receptor FUNDC1 associates with ER‐resident protein calnexin and thereby accumulates at the ER–mitochondrial contact site; this allows for DRP‐1 recruitment and thus mitochondrial fission.